Biological fabrication of zinc oxide nanoparticles from Nepeta cataria potentially produces apoptosis through inhibition of proliferative markers in ovarian cancer - Gu Wenli; Li Haining; Niu Xianyi; Zhou Jianyun (Green Processing and Synthesis, 2022)
This study evaluated the biological fabrication and characterization of zinc oxide nanoparticles (ZnONPs) using Nepeta cataria (NC) and their anticancer activity against ovarian cancer cells (SKOV3). This study synthesized ZnONPs using leaf extract of N. cataria through a biological method. The synthesized particles were characterized in several ways such as zeta potential, ultraviolet-visible (UV-Vis) spectrum, Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopic (SEM) analysis. UV-Vis spectrum exhibited that maximum spectra were found to be 380 nm. The size of the material was shown to be 75.9 nm confirmed by dynamic light scattering measurement. Moreover, XRD, SEM, and transmission electron microscopic analysis were confirmed by the synthesized materials as crystal-based ZnONPs. FTIR studies represent that several biologically active functional groups existed in the synthesized nanoparticles. In addition, the anticancer ability and the inhibitory role of ZnONPs-NC against SKOV3 cells were investigated. We found that ZnONPs-NC causes efficient toxicity in SKOV3 cells by increasing cytotoxicity depending on reactive oxygen species production and nuclear fragmentation in SKOV3 cells. ZnONPs-NC activates Bax and Caspases while inhibiting Bcl-2 proteins in SKOV3 cells. Furthermore, we discovered that ZnONPs-NC inhibits the proliferative markers PCNA, cyclin-D1, matrix metallo proteinase (MMP)-2, and MMP-9) in SKOV3 cells. Thus, biologically synthesized ZnONPs-NC were found to be effectively inhibiting ovarian cancer cell growth.